Abstract 1122‐000205: Bilateral ACA Stroke ‐ A Case Report of an Unusual Presentation - Tejeswi Suryadevara; Bhavya Narapureddy; Carlos Y Lopez; Karen C Albright (Stroke: Vascular and Interventional Neurology, 2021)
Introduction: Bilateral ACA strokes are rare, with one stroke registry reporting 2 cases out of 1490 strokes (1). These strokes are even less common in the absence of anatomic variants, such as an azygos ACA. Diagnosis may be difficult given the variability in clinical presentation. Methods: This is a case report. Results: A 51‐year‐old right handed man with no cerebrovascular risk factors on no antithrombotic medications presented two hours from last known well with complaints of generalized weakness, inability to speak or move, and feeling numb all‐over during intercourse. He reported rapid improvement in symptoms. Emergency room exam was notable for right leg weakness (3/5) and left leg plegia with intact sensation. Hoover’s sign was positive in the left leg and the patient was able to bear some weight while standing with a two‐person assist. A computed tomography angiogram (CTA) of his head and neck was preliminarily interpreted as normal. No azygos ACA or single internal carotid artery origin for the ACAs were present. His exam improved to an isolated left foot dorsiflexor and plantar flexor weakness. The decision was made not to use thrombolytics based on his symptoms and exam which were improving and not entirely consistent with acute stroke. Brain magnetic resonance imaging demonstrated bilateral parasagittal acute strokes. It was later noted the that non‐contrast head CT demonstrated bilateral hyperdense ACAs. Conclusions: This case demonstrates the difficulty in diagnosing bilateral ACA infarcts in a previously healthy adult in the setting of whole‐body numbness and positive Hoover’s sign. In retrospect, his transient inability to speak or move may have been transient akinetic mutism or callosal disconnection syndrome. Additionally, this case emphasizes the importance of evaluating for the hyperdense ACA sign (2) in patients complaining of bilateral leg weakness.